Balancing Spiritual Leadership and Modern Management Practices: A Hybrid Model for Educational Excellence in Islamic Schools - Arman Paramansyah; Lussi Avianti (JUMPA : Jurnal Manajemen Pendidikan, 2026)
The increasing demands for educational quality and institutional competitiveness have prompted Islamic schools to integrate spiritual leadership with modern management practices to strengthen organizational effectiveness and sustainability. This study aims to analyze the integration of spiritual leadership and modern management practices in strengthening institutional effectiveness in Islamic schools. This study uses a qualitative case study approach with data collected through observation, semi-structured interviews, documentation review, and institutional records. Data analysis uses the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the integration of spiritual leadership and modern management practices significantly improves school performance through strategic planning, an ethical organizational culture, and a quality assurance system. Spiritual leadership strengthens teacher commitment by fostering emotional attachment, intrinsic motivation, and organizational loyalty among educators. A modern governance system integrated with Islamic values enhances accountability, transparency, administrative efficiency, and participatory decision-making within schools. This study contributes theoretically by proposing an integrative framework linking spirituality and educational management in Islamic institutions.